1994
DOI: 10.1248/bpb.17.866
|View full text |Cite
|
Sign up to set email alerts
|

Anti-aging Effect of DX-9386 in Senescence Accelerated Mouse.

Abstract: The effects of DX-9386, a traditional Chinese prescription (ginseng, acorus, polygala and hoelen) were studied on life span, the degree of senescence, motor activity and the antibody production response in senescence accelerated mouse (SAM). DX-9386-containing food was given to SAM for 13 consecutive months from 2 months of age. DX-9386 significantly prolonged the life span of SAM, prevented body weight decrease with aging and tended to improve the senile syndrome. The motor activity of SAMP8 was higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…18) Hoelen, another component of Hachimi-jio-gan and Juzen-taiho-to, had anti-aging impact, prolonged the life span of SAM, prevented body weight decrease with aging and tended to improve the senile syndrome. 19) However, there have been no reports on the treatment or prevention of senile osteoporosis by these herbal medicines.…”
Section: )mentioning
confidence: 99%
“…18) Hoelen, another component of Hachimi-jio-gan and Juzen-taiho-to, had anti-aging impact, prolonged the life span of SAM, prevented body weight decrease with aging and tended to improve the senile syndrome. 19) However, there have been no reports on the treatment or prevention of senile osteoporosis by these herbal medicines.…”
Section: )mentioning
confidence: 99%
“…11,12) Roots and rhizomes of Acorus calamus LINN (AC), commonly known as sweet flag, sweet grass and sweet cane (Family: Araceae), have been used in the Indian and Chinese systems of the medicine for hundreds of years for its beneficial role in improved learning performance, and its anti-aging effect. [13][14][15] Shukla et al reported that ethanolic extract of AC prevented acrylamide-induced hind limb paralysis, decreased GSH and GST, increased dopamine receptors in the corpus striatum.…”
mentioning
confidence: 99%
“…Extract of Ginko biloba enhance retention memory, in scopolamine-induced amnesia in both young and old rats and improved short-term memory in mice (Chopin and Briley, 1992;Petkov et al, 1993). DX-9386 (Chinese traditional prescription containing P. tenuifolia) improved motor activity, reduced lipid peroxidation, ameliorated memory impairment and prolonged the life span of senescence-accelerated mice in ethanol and scopolamine induced memory impairment in mice Zhang et al, 1994). Extract of Nelumbo nucifera improves retention memory by inhibiting acetylcholinesterase (AChE) activity in scopolamine-induced amnesia in rats (Oh et al, 2009).…”
Section: Plants Beneficial In Cognitive Declinementioning
confidence: 99%